Nutritional Support and Probiotics as a Potential Treatment of IBD - Tarasiuk, Aleksandra; Eibl, Guido (Current Drug Targets, 2020)
The pathogenesis of inflammatory bowel disease (IBD) remains unknown. However, there is growing evidence that the increase in the overall incidence of IBD relates to the improvement of sanitary and hygienic conditions of the society leading to lower exposure to both bacterial and parasitic infections. IBD is incurable and characterized by alternating periods of exacerbation and remission of symptoms. Therefore, the main goal of treatment strategies in IBD patients is the most effective maintenance of clinical and endoscopic remission, which does allow patients to function normally for a significant part of life. Taking into account the evidence from different areas, there is a strong rationale supporting the concept that bacteria are important in gut inflammation and that probiotic bacteria may modulate the host-microbe interaction in a way that is directly beneficial to IBD patients along with nutritional support. In this review, we focus on the potential role of gastrointestinal microbiota in the pathogenesis of IBD and the possible value of probiotics, prebiotics, and symbiotics as well as nutritional support in the treatment of IBD.
Keywords: ulcerative colitis